‘Wednesday was just a beautiful day’: A Feminist Classroom as a Space to Engage with Social Struggles in the Italian Academy - salimbeni, alice (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
Passive academic education undermines students’ authority to voice their opinions and, consequently, limits their ability to foster critical thinking, reducing universities to mere factories of subordination (Borghi and the Brigata SCRUM, 2020). Rather than promoting passive knowledge transfer, feminist pedagogies call for transforming the classroom into a space where both students and teachers work together to challenge systemic injustices. Drawing on feminist pedagogy, in this paper, I argue for a practical approach to create feminist classrooms within neoliberal universities as spaces where to engage with social struggles, with a particular focus on Italian academia. This paper contributes to the growing body of work on feminist pedagogy, broadening the discourse beyond the Anglophone focus. Additionally, I contribute to a repository of feminist teaching experiences that can be drawn upon by those committed to the effort of creating feminist and subversive learning spaces.